3 - Identity and Knowledge Production in the Fourth Generation - Anyidoho, Nana Akua (Africa Development, 2009)
This paper examines the linked themes of identity and knowledge production embedded within the concept of insider scholarship. Insider scholarship may be described as the production of knowledge by a scholar about a group with which s/he identifies as a member. We are immediately compelled to complicate this definition by asking how any such group is delineated and how member- ship therein shapes knowledge production. The idea of insider scholarship thus evokes a series of queries about who produces what knowledge, about whom and for whom. The paper makes the argument that the discussion on insider scholarship has gained renewed relevance. In an effort to reclaim representa- tions of Africa and Africans, earlier generations of African scholars might some- times have based scholarly legitimacy on idealisations of race, culture and terri- tory. From that historical point, we appear to be in a moment when notions of ‘cosmopolitanism’ and ‘universalism’ make nonsense of any attempt to ground scholarship in complex and shifting identities. As the fourth generation of scholars comes into its own, one of its defining tasks will be to negotiate this contested terrain. This paper represents such an attempt. It argues that the concept of insider scholarship cannot simply be discarded as irrelevant. To do so would constitute an ill-advised neglect or woeful ignorance of the politics of represen- tation about Africa, and of the power differentials in different spaces within the field of African Studies. However, there are multiple grounds for claiming ‘insiderness’, and defining it by narrow parameters is unhelpful, if not damaging to any sense of common purpose. In light of this, I present ‘shared struggle’ as a strategic basis for reconstituting the theoretical value and the viable practice of insider scholarship. I conclude the paper by examining the implication of this conceptual shift.